Von Neumann Algebra Preduals Satisfy the Linear Biholomorphic Property - Peralta, Antonio M.; Stachó, László L. (MATHEMATICA SCANDINAVICA, 2016)
We prove that for every JBW^*-triple E of rank >1, the symmetric part of its predual reduces to zero. Consequently, the predual of every infinite dimensional von Neumann algebra A satisfies the linear biholomorphic property, that is, the symmetric part of A_* is zero.